Smart With Islamic Communication Methods In The Review Of Muslimic Conscience In Youth Children In Lubuk Pakam I/II - Wafa, Aulia; Rubino, Rubino (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
This study aims to find out how the method of communication Smart with Islamic in increasing the consciousness of Muslims among teenagers in the Lubuk Pakam I/II. The source of the researched data is the manager of the study Smart with Islamic Lubuk Pakam total of 5 people. The method used is a qualitative research method by explaining and exposing research through observations, interviews and documentation. The results of this study showed that within the Muslims the priority is not about proper or not, but the commitment to Muslims (responsible) rules whose rules come from the rules of Allah SWT is not the coming of human rules.